A narrative review of research advances in gut microbiota and microecological agents in children with attention deficit hyperactivity disorder (ADHD) - Liu, Yang; Zhang, Panpan; Sun, Hao (Frontiers in Psychiatry, 2025)
The role of gut microecology in attention deficit hyperactivity disorder (ADHD) has garnered growing attention. Studies have suggested a potential link between ADHD development and an imbalance in gut microbiota composition. This review aims to analyze the characteristics of the gut microbiota in children with ADHD, explore how changes in the gut microbiota affect ADHD through nervous, neuroendocrine, and immune pathways, and discuss the potential application of microecological agents and fecal microbiota transplantation in the prevention and treatment of ADHD in children. Pubmed, Google Scholar, EBSCO, Scopus and Medline were utilized to conduct searches using the following key terms:Attention Deficit Hyperactivity Disorder OR ADHD AND gut microbiota OR probiotics OR prebiotics OR synbiotics OR fecal microbiota transplantation OR FMT. Studies published in English from all years were included. A thorough review of numerous papers and their references was conducted to identify relevant articles. Sorting and analysis revealed that the gut microbiota of children with ADHD has changed to some extent, and targeting the gut microbiota, using microecological agents or fecal microbiota transplantation, especially in combination with central nervous system stimulants, may provide additional benefits for children with ADHD.